Sejarah Perkembangan Tarikat Qadiriyah: Ajaran, Zikir/Wirid Dan Metodenya - Muhammad Isrha; Rahmi Damis; Hamzah Harun (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the historical development of the Qadiriyah Sufi order, its teachings, dhikr, wirid, and methods, including the practice of dhikr, the form of initiation (bay‘ah), and its institutional structure. The research method involves a literature review, analysis of previous studies, and discussions. The purpose of this study is to understand the history of the development of the Qadiriyah order, the methods, teachings, and aspects of Sufi thought taught within the Qadiriyah order, as well as the process of its development and dissemination. The results of this study, viewed from several aspects using a Sufistic approach, indicate that the Qadiriyah order emerged as a response to anomalies in the social reality of its time. Historically, this order continued to develop and eventually became one of the largest religious movements accompanying the growth of Islamic culture within society. Shaykh ‘Abd al-Qadir al-Jilani believed that a noble life is achieved by devoting oneself solely to God. A God-conscious existence provides spiritual strength that redirects one from worldly pleasures toward spiritual happiness. In his efforts to emphasize self-purification from worldly desires, Shaykh ‘Abd al-Qadir al-Jilani outlined several guidelines to attain the highest level of self-purity through seven principles: repentance, asceticism (zuhd), trust in God (tawakkul), gratitude, patience, contentment (ridha), and honesty.